The Effect of Financial Literacy, Income, and Risk Perception on Investment Decisions in Gold Installment Products among Generation Z in the Bandung Metropolitan Area - Nuryani, Wulan; Mauluddi, Hasbi Assidiki (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The objective of this study is to determine the influence of financial literacy, income, and risk perception on gold investment decisions among Generation Z in the Greater Bandung area. Financial literacy is measured through knowledge and behavior, income is measured through salary/wages, and risk perception is measured through fraud risk. The research method used is quantitative, employing purposive sampling and data collection via a questionnaire, yielding 100 respondents, with results calculated using the Lemeshow formula. Data analysis was conducted using SEMPLS with the SmartPLS application to determine how financial literacy, income, and risk perception collectively influence gold investment decisions. Descriptive quantitative analysis was used to explain the phenomena studied in this research. It is hoped that the researcher can provide an understanding of financial literacy, income, and risk perception in relation to gold investment decisions. This study found that financial literacy influences gold investment decisions, income influences gold investment decisions, and risk perception influences gold investment decisions.